Determining Covid-19 Disaster Preparedness in Students in Makassar City - Maria, Ida Leida; Pratiwi, Indrakasih; Nauval Hafizh Thaha, Adhi; Jaharuddin, A. Rinaldy; Selvi Yusnitasari, Andi; Irabuana; Auliya Muthmainnah, Lolah; Qura, Ummul (Media Kesehatan Masyarakat Indonesia, 2020)
Covid-19 is a disease that has become a pandemic that is very troubling at this time, including in Indonesia, which until July 16, there were 81,668 with a total of 3,873 deaths. This study aims to determine the determinants that affect the preparedness of the Covid-19 Pandemic among students in Makassar City. The study was conducted in an observational manner with a cross sectional study approach. Sampling in this study was conducted using non probability sampling technique, namely consecutive sampling. This research was conducted at 8 universities in Makassar City from April to July 2020. The type of data collection used accidental sampling. The results of data collection in this study were processed using the Stata 16 application which was analyzed univariately and bivariately. The results of data processing are presented in the form of tables and are equipped with narration. The results in this study indicate that there is a relationship between Covid-19 preparedness and knowledge (p=0.049), experience (p=0.013), attitude of respondents (p=0.018). The conclusion of this study is that knowledge, experience and attitude are determinants of Covid-19 preparedness. The author's suggestion is that the government can improve education and efforts to implement prevention by the community.